An Integrated Quantitative Index for Measuring Chronic Multisite Pain: The Multiple Areas of Pain (MAP) Study. Issue 7 (21st February 2018) - Wallace, Mark S; North, James; Grigsby, Eric J; Kapural, Leonardo; Sanapati, Mahendra R; Smith, Stephen G; Willoughby, Channing; McIntyre, Patrick J; Cohen, Steven P; Rosenthal, Richard M; Ahmed, Shaik; Vallejo, Ricardo; et al.
Abstract: Objective: Despite the high prevalence of chronic multisite pain, there is little consensus on methods to characterize it. Commonly used assessments report only one dimension of pain, that is, intensity, thus ignoring the spatial aspect of pain. We developed a novel pain quantification index, the Integrated Pain Quantification Index (IPQI), on a scale of 0 to 1 that integrates multiple distinct pain measures into a single value, thus representing multidimensional pain information with a single value. Design: Single-visit, noninterventional, epidemiological study. Setting: Fourteen outpatient multidisciplinary pain management programs. Patients: Patients with chronic pain of the trunk and/or limbs for at least six months with average overall pain intensity of at least 5 on the numeric rating scale. Methods: Development of IPQI was performed in a large population (N = 810) of chronic pain patients from the Multiple Areas of Pain (MAP) study. Results: Prevalence of two or more noncontiguous painful areas was at 88.3% (95% confidence interval [CI] = 0.86–0.90), with a mean of 6.3 areas (SD = 5.57 areas). Prevalence of more than 10% body area in pain was at 52.8% (95% CI = 0.49–0.56), with a mean at 16.1% (17.16%). On average, IPQI values were near the middle of the scale, with mean and median IPQI at 0.52 (SD = 0.13) and 0.55, respectively. The IPQI was generalizable and clinically relevant across all domains recommended by the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials. Conclusions: IPQI provided a single pain score for representing complex, multidimensional pain information on one scale and has implications for comparing pain populations across longitudinal clinical trials.